RESEARCH ON KEY PARAMETER FOR FORKLIFT STABILITY - GAI YanQing; PANG RuiFeng; DONG DanPeng; REN YanRu; LIU ChengJiang (Jixie qiangdu)
Counterbalanced forklifts is a kind of industrial vehicles specially used for handling, loading and unloading, having a wide range of uses, and the working environment is becoming more and more complex. Research on the stability of counterbalanced forklifts is becoming more and more important, but stability has attracted less attention in the academic community. The deflection of portal frame channel steel is a key parameter of stability that cannot be ignored. Domestic design of portal frame channel steel is based on analogy, which leads to its high safety factor, waste of raw materials, and weak theory and computer assistance. This paper analyzes the influence on safety and stability of the counterbalance forklift, and studies the longitudinal stacking stability of the forklift. Through the force and deformation analysis of the forklift channel beam, a model of the longitudinal stability and deflection deformation of the channel steel is established. Verify the correctness of the model through experiments. Research on the stability of counterbalanced forklifts provides theoretical basis and guidance for enterprises in the design and development of forklifts, which is conducive to saving materials, improving the energy efficiency of forklifts and ensuring their safety and reliability. It has certain theoretical significance and engineering value.